Analisis Nilai Karakter Integritas Pada Proyek Penguatan Profil Pelajar Pancasila Era Society 5.0 Kelas VI SD Islam Imama - Wulandari, Fenita Mei; Cahyani, Yuni Nur; Hapsari, Fitra Hesti; Wulandari, Nevita; Kiptiyah, Siti Maryatul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to analyze the formation of integrity character through the Pancasila student profile strengthening project in preparation for the era of society 5.0. In this research, the author uses qualitative research using library research methods. Data analysis uses interactive techniques from Miles, Huberman, and Saldana with three stages, namely data condensation, data display, and conclusion drawing. The results showed that the formation of integrity character through (p5) activities towards the era of society 5.0 can make individuals who have the character of honesty, responsibility, moral commitment, justice, exemplary, loyal, anti-corruption, and love for the truth. So the implementation of integrity character building in schools must be carried out properly to improve these characters and can increase competitiveness, as well as the attractiveness of individuals who do not forget the foundation of the philosophy of life of the nation and state in the formation of the integrity character of the current generation.